Ethical dilemmas in education: a case study of challenges faced by secondary school leaders in Kenya. Issue 6 (9th May 2019) - Oduol, Truphena; Cornforth, Sue
Abstract : Purpose: The purpose of this paper is to question the usefulness of Euro-Western concepts of principled ethical behaviour for school leaders in non-Euro-Western countries by examining the dilemmas faced by Kenyan educational leaders. Design/methodology/approach: A single, multi-site case study methodological approach was used, and data gathered by means of semi-structured interviews with stakeholders: school principals, boards of governors, heads of department, school bursars and parents. Findings: Findings highlighted the importance of contextual variables in influencing leaders' decisions, indicative of the tension between liberal and communitarian ethical approaches. Although similar dilemmas were encountered to those working in euro-western contexts, Kenyan educational leaders faced the additional challenge of working with cultural values of Ubuntu: care for the whole community, harmonious working relationships, loyalty to one's kin and respect of seniority. Furthermore, the problems they encountered were often life-threatening resulting from poverty, and HIV/Aids. Originality/value: This paper contributes to the literature on ethics in educational leadership by proposing that the adoption of euro-western ethical standards and perspectives in non-Euro-Western countries is problematic, unless mitigated by a dialogic approach.